Imposing risk : a normative framework - Oberdiek, John (Oxford : Oxford University Press, 2017)
When we impose risk upon others, what are we doing? What is risking's moral significance? What moral standards govern the imposition of risk? And how should the law respond to it? This book constructs a normative framework of risk imposition to help answer these important and oft-ignored questions.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 15, 2017).
Keywords: Law -- Philosophy; Risk -- Moral and ethical aspects; Law; Jurisprudence & general issues